Sistem Temu Kembali Informasi dengan Pemeringkatan Metode Vector Space Model - Fathkul Amin (Universitas Stikubank, 2013)
The objective of designing information retrieval system (IRS) with Vector Space Model (VSM) Method is to facilitate users to search Indonesian documents. IRS Software is designed to provide search results with the optimum number of documents (low recall) and accuracy (high precision) with VSM method that users may get fast and accurate results. VSM method provides a different credit for each document stored in a database which in turns to determine the document most similar to the query, where the documents with the highest credits are placed on the top of the search results. The evaluation of search results with IRS is conducted under recall and precision tests. This study fascinatingly creates a system which can preprocess (tokenizing, filtering, and stemming) within computation time of four minutes forty-one seconds. Keywords: IRS, Vector Space Model, recall, precision